2016
DOI: 10.1016/j.heliyon.2016.e00222
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression alterations in the medial prefrontal cortex and blood cells in a mouse model of depression during menopause

Abstract: AimsThe prevalence of major depressive disorder (MDD) is higher in women than in men, and this may be due to the decline in estrogen levels that occurs during the menopausal transition. We studied the biological alterations in the medial prefrontal cortex (mPFC), which is a region that is highly implicated in the neurobiology of MDD, and the blood cells (BCs) of ovariectomized (OVX) mice subjected to chronic mild stress (CMS), which represents a mouse model of depression during menopause.Main methodsThe mPFC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…The majority of rodent studies involving behavioral analyses used male rodents, despite a higher prevalence of MDD in women. Future investigations will require the inclusion of both sexes in animal testing (Hodes et al, 2017 ), but it is interesting to note that in a mouse model of depression during menopause, Miyata et al ( 2016b ) also found that the gene expression alterations induced by ovariectomy were mainly associated with ribosomal and mitochondrial functions in both the medial prefrontal cortex and the blood, strengthening the results we discussed above. We also only addressed the response to antidepressant treatment with a single drug, fluoxetine, while other drugs with different selectivity for neurotransmitters other than serotonin are frequently used in the clinic (Bagot et al, 2017 ).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The majority of rodent studies involving behavioral analyses used male rodents, despite a higher prevalence of MDD in women. Future investigations will require the inclusion of both sexes in animal testing (Hodes et al, 2017 ), but it is interesting to note that in a mouse model of depression during menopause, Miyata et al ( 2016b ) also found that the gene expression alterations induced by ovariectomy were mainly associated with ribosomal and mitochondrial functions in both the medial prefrontal cortex and the blood, strengthening the results we discussed above. We also only addressed the response to antidepressant treatment with a single drug, fluoxetine, while other drugs with different selectivity for neurotransmitters other than serotonin are frequently used in the clinic (Bagot et al, 2017 ).…”
Section: Discussionsupporting
confidence: 56%
“…Daskalakis et al ( 2014 ) demonstrated convergent signaling pathways between the blood and the brain (amygdala and hippocampus) associated with trauma-related individual differences in a rat model of posttraumatic stress disorder. Apart from a recent study comparing gene expression alterations in the medial prefrontal cortex and blood cells of ovariectomized mice subjected to chronic mild stress (Miyata et al, 2016b ), to our knowledge, our study is the first to report central and peripheral transcriptional signatures associated with response to antidepressant treatment in an animal model of major depression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The majority of rodent studies involving behavioral analyses used male rodents, despite a higher prevalence of MDD in women. Future investigations will require the inclusion of both sexes in animal testing (Hodes et al, 2017), but it is interesting to note that in a mouse model of depression during menopause, Miyata et al (2016b) also found that the gene expression alterations induced by ovariectomy were mainly associated with ribosomal and mitochondrial functions in both the medial prefrontal cortex and the blood, strengthening the results we discussed above. We also only addressed the response to antidepressant treatment with a single drug, fluoxetine, while other drugs with different selectivity for neurotransmitters other than serotonin are frequently used in the clinic (Bagot et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…Daskalakis et al (2014) demonstrated convergent signaling pathways between the blood and the brain (amygdala and hippocampus) associated with trauma-related individual differences in a rat model of posttraumatic stress disorder. Apart from a recent study comparing gene expression alterations in the medial prefrontal cortex and blood cells of ovariectomized mice subjected to chronic mild stress (Miyata et al, 2016b), to our knowledge, our study is the first to report central and peripheral transcriptional signatures associated with response to antidepressant treatment in an animal model of major depression.…”
Section: Discussionmentioning
confidence: 99%